2014
DOI: 10.3390/vetsci1010040
|View full text |Cite
|
Sign up to set email alerts
|

Non-Human Primate Models of Orthopoxvirus Infections

Abstract: Smallpox, one of the most destructive diseases, has been successfully eradicated through a worldwide vaccination campaign. Since immunization programs have been stopped, the number of people with vaccinia virus induced immunity is declining. This leads to an increase in orthopoxvirus (OPXV) infections in humans, as well as in animals. Additionally, potential abuse of Variola virus (VARV), the causative agent of smallpox, or monkeypox virus, as agents of bioterrorism, has renewed interest in development of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 93 publications
(131 reference statements)
0
14
0
Order By: Relevance
“…In collaboration with the Robert Koch Institute (RKI), a cow pox virus was isolated. Sequence analyses and phylogenetic investigations showed that it was a novel cow pox virus, which was named calpox virus after its host species ("Callithrix") (Mätz-Rensing et al, 2006Kramski et al, 2010;Schmitt et al, 2014).…”
Section: New Trends Of Researchmentioning
confidence: 99%
“…In collaboration with the Robert Koch Institute (RKI), a cow pox virus was isolated. Sequence analyses and phylogenetic investigations showed that it was a novel cow pox virus, which was named calpox virus after its host species ("Callithrix") (Mätz-Rensing et al, 2006Kramski et al, 2010;Schmitt et al, 2014).…”
Section: New Trends Of Researchmentioning
confidence: 99%
“…Therefore, development of medical interventions and new vaccine strategies and studies on pathogenesis are essential and require animal models, on which the efficacy of new vaccines and therapeutics can be tested. Over the last few decades, considerable progress has been made in developing small animal and nonhuman primate models with different OPXV, among them variola; but none fully mimic the natural route or course of infection in humans [ 30 , 31 , 32 , 33 , 34 ]. The advantage of small animal models is that larger numbers of animals can be used at lower maintenance costs compared to nonhuman primate models.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades several animal models for OPXV were developed in NHPs (Schmitt et al, 2014). Unfortunately, none of the animal models fulfills all the criteria needed and all have limitations (Hutson and Damon, 2010;Safronetz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Key events of a natural pox infection such as the alteration of the upper respiratory tract, a primary viremic phase and prodromal phases are skipped. Nevertheless, these models cause a systemic disease with mortality rates of up to 100 % and can be used to evaluate the efficacy of anti-OPXV therapeutics (Huggins et al, 2009) and vaccines (summarized in Schmitt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%